PALEOSCENE 13. Paleopathology of Vertebrates: Insights to Lifestyle and Health in the Geological Record - Rothschild, Bruce; Tanke, Darren (Geoscience Canada, 1992)
Summary Study of ancient disease (paleopathology) is a powerful tool for understanding lifestyle and population dynamics, as well as the history of disease in antiquity. The major premise of paleopathology is that diagnoses of conditions of living animals can be extrapolated to fossils. Recognition of persistence of structural integrity, and even of cellular components, allows use of new radiologic, immunologic, DNA and holistic analysis techniques to effectively test diagnostic impressions. Collaboration by specialists instructural relationships (e.g., paleontologists) and students of disease (e.g., healthcare providers) provides significant insights to behaviour of animals, long since extinct.